Detection of H2O and CO2 in the Atmosphere of the Hot Super-Neptune WASP-166b with JWST - Andrew W. Mayo; Charles D. Fortenbach; Dana R. Louie; Courtney D. Dressing; Emma V. Turtelboom; Steven Giacalone; Caleb K. Harada (The Astronomical Journal)
We characterize the atmosphere of the hot super-Neptune WASP-166b ( P = 5.44 days, R _p = 6.9 ± 0.3 R _⊕ , M _p = 32.1 ± 1.6 M _⊕ , T _eq = 1270 ± 30 K) orbiting an F9V star using JWST transmission spectroscopy with NIRISS and NIRSpec (0.85–5.17 μ m). With this broad wavelength range, NIRISS provides strong constraints on H _2 O and clouds (where NIRSpec performs poorly) while NIRSpec captures CO _2 and NH _3 (where NIRISS performs poorly). Our POSEIDON free chemistry retrievals confirm the detection of H _2 O (15.2 σ significance) and detect CO _2 (14.7 σ ) for the first time. We also find a possible hint of NH _3 (2.3 σ ) and an intermediate pressure cloud deck (2.6 σ ). Finally, we report inconclusive support for the presence of SO _2 , CO, and Na, as well as nondetections of CH _4 , C _2 H _2 , HCN, H _2 S, and K. We verify our results using a TauREx free chemistry retrieval. We also measure with POSEIDON equilibrium chemistry retrievals a superstellar planetary atmospheric metallicity ( $log\,(Z)=1.5{7}_{-0.18}^{+0.17}$ , $Z=3{7}_{-13}^{+18}$ ) and planetary C/O ratio ( ${\rm{C}}/{\rm{O}}=0.28{2}_{-0.053}^{+0.078}$ ) consistent with the stellar C/O ratio (C/O _* = 0.41 ± 0.08). These results are compatible with various planetary formation pathways, especially those that include planetesimal accretion followed by core erosion or photoevaporation. WASP-166b also resides near the edge of the Hot Neptune Desert, a sparse population of intermediate-sized planets at high insolation fluxes; thus, these results and further atmospheric observations of Hot Neptunes will help determine the driving processes in the formation of the Hot Neptune Desert.